If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15y + -3 = 29 + -1y Reorder the terms: -3 + 15y = 29 + -1y Solving -3 + 15y = 29 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. -3 + 15y + y = 29 + -1y + y Combine like terms: 15y + y = 16y -3 + 16y = 29 + -1y + y Combine like terms: -1y + y = 0 -3 + 16y = 29 + 0 -3 + 16y = 29 Add '3' to each side of the equation. -3 + 3 + 16y = 29 + 3 Combine like terms: -3 + 3 = 0 0 + 16y = 29 + 3 16y = 29 + 3 Combine like terms: 29 + 3 = 32 16y = 32 Divide each side by '16'. y = 2 Simplifying y = 2
| 17b-8=0 | | x-18+2(x+2)=6x+24 | | 4(4x-1)=2(8x+6) | | 5+4z-3=9z+8-6z | | -3y-2=-5-4y | | 5z+4(4-z)=-(2-4)+10 | | 9+2m=99-8m | | 225=144-24x+x^2+81+18x+x^2 | | 225=144-24x+x^2+81+18x+x | | P=2(96)+2(99) | | 5z+4(4-2)=-(2-4)+10 | | I=(400)(.14)(2) | | 2m^2-5m+2=0 | | 7r+9r=112 | | -144=-9d | | (5x^2-x+2)-(x^2+6x-8)=0 | | -4(3b+1)+(13b-9)=0 | | 20-7s=26-8s | | 5x+4-2x=28 | | 3x^2-x=-6 | | 2z-4(z+1)=-5(5z+6)+z | | 5.3x-1.5-5.6x=1.3x-4.4 | | 11(6m+3p)=4(12m+5p) | | -2-27=29 | | 2(3)-3y=12 | | 2x-2.4=3.6 | | (3)2-2(11-8)2=36x | | 111=6x-4x-9 | | r^2+2rs+s^2-9= | | 37(21y+14)-3(4y+4)=0 | | x+(x+450000)=625000000 | | -8+z=-46 |